(untitled) (Comillas Journal of International Relations, 2019)
The joining of Spain to the European Economic Community was a strategic aim of his foreign policy in the 20th century. This process meant on the one hand a political change and on the other hand a very deep economic adjustment. These negotiations were more complex and difficult than the new democratic Spain could expect. The role of France in the process has been widely recognised. However, other countries played also an important role, especially the Federal Republic of Germany, the other large member of the Common Market. In this paper we analyse the position of the FRG in the first years of the negotiation from the point of view of the Spanish negotiators themselves. This paper has the basis on the Archive of Leopoldo Calvo-Sotelo, first minister for Relations with the European Communities.